1997
DOI: 10.1021/jp970029y
|View full text |Cite
|
Sign up to set email alerts
|

Substituents Effect on the Electronic Properties of Aniline and Oligoanilines

Abstract: Aniline oligomers have been intensively studied in the past years. In particular, aniline oligomers substituted with electron-donor groups have been synthesized and its electronic properties calculated. However, when an electron-acceptor group is attached to the benzenoid ring of the oligoaniline, strong effects over its electronic properties are expected to happen. In this work some semiempirical quantum chemistry calculations of geometric structures, and energy level distribution of aniline and substituted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 46 publications
0
40
0
Order By: Relevance
“…A number of communications tackle quantum chemical models of isolated PANI oligomers of different length and oxidation state 5–9. They discuss geometry, electronic structure, conductivity, and optical absorption of various oligomers ranging from dimers to dodecamers.…”
Section: Introductionmentioning
confidence: 99%
“…A number of communications tackle quantum chemical models of isolated PANI oligomers of different length and oxidation state 5–9. They discuss geometry, electronic structure, conductivity, and optical absorption of various oligomers ranging from dimers to dodecamers.…”
Section: Introductionmentioning
confidence: 99%
“…The only other theoretical work known on substituent effects in polyanilines is that of Vaschetto and Retamal. [21] Their work on the oligoaniline tetramer using the semi-empirical PM3 method concluded that 2-and 3-substitution with methoxy, methyl, fluoro, cyano, and nitro groups leads to significant changes in both the geometric and electronic structure of oligoaniline systems. To some extent, our work agrees with their calculations though we use a somewhat different approach and a more advanced methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Recent theoretical works investigated the structural and electronic properties of substituted aniline oligomers [20,21,24,25]. Oligomers of aniline are considered electron donors, especially the emeraldine form [20].…”
mentioning
confidence: 99%